"Doing one's work" in entrepreneurship studies: interpellation, distraction, disruption and transformation. Issue 3 (14th September 2021) - Martinez Dy, Angela
Abstract : Purpose: This paper takes seriously the feminist adage that "the personal is political" by critically exploring my experiences as an early career scholar of gender and entrepreneurship studies to offer vital context for the contributions of my work and future research agenda, in light of the current historical moment of interconnected political, public health and environmental calamity. Design/methodology/approach: The author presents reflections on her positionality, philosophical and political commitments, and theorises from her experiences of racist distraction and intersectional marginality in contemporary academia, considering their implications for incoming and aspiring gender and entrepreneurship scholars whose research agendas are still in development. Findings: Racism functions as a persistent distraction from overall research agendas and activities, and delimits the lane of perceived contributions. However, collectively challenging it in work and study presents a vehicle by which intellectual and affective experiences of academic work may be enriched, and a spacious and expansive legacy of critical scholarship built that will be resonant for years to come. Originality/value: The paper argues that although racism will doubtlessly continue to cause immense distraction, it presents an invitation to create positive social change, through collectivising with a community that aims to shape a liveable, equitable and imaginative academic future.